1997
DOI: 10.1108/13639519710169162
|View full text |Cite
|
Sign up to set email alerts
|

Police tactics in incidents with mentally disturbed persons

Abstract: IntroductionSince the 1950s developments in psychiatry and law have returned most mentally disturbed people to community settings. One consequence has been an increase of incidents in which police officers must intervene to control mentally disturbed people. In New York City, for example, incidents involving "emotionally disturbed persons" (EDPs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…This perspective articulates the position that because officers are unfamiliar with managing PMI-related incidents (e.g., lack training and self-confidence), traditional techniques such as communicating directives and negotiation are less effective. Officers have been shown to believe that PMI lack rationality and are more inclined to violence than persons without mental illness (Panzarella & Alicea, 1997; Ruiz & Miller, 2004; Slate, Buffington-Vollum, & Johnson, 2013). These beliefs about PMI may result in an increased level of fear among officers in the management of incidents involving citizens with mental illness.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This perspective articulates the position that because officers are unfamiliar with managing PMI-related incidents (e.g., lack training and self-confidence), traditional techniques such as communicating directives and negotiation are less effective. Officers have been shown to believe that PMI lack rationality and are more inclined to violence than persons without mental illness (Panzarella & Alicea, 1997; Ruiz & Miller, 2004; Slate, Buffington-Vollum, & Johnson, 2013). These beliefs about PMI may result in an increased level of fear among officers in the management of incidents involving citizens with mental illness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These beliefs about PMI may result in an increased level of fear among officers in the management of incidents involving citizens with mental illness. Fear and apprehension may lead officers to use more aggressive tactics due to a belief that situations involving PMI “are not amenable to more moderate tactics” (Panzarella & Alicea, 1997, p. 335), resulting in higher levels of force being used on PMI and more frequent citizen injuries. Officers may also fail to recognize that a citizen's behavior is symptomatic of a mental illness and may therefore place that person in the asshole category rather than being more sympathetic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies provided corroborating evidence that officers have used this method of resolving disturbances involving people with mental disorders. Evidence existed that this technique of "dumping" mentally disordered individuals in other jurisdictions was also sometimes considered preferential (in the minds of some officers) to making an arrest (Panzarella & Alicea, 1997;Ruiz, 1993). Some officers view transporting troublesome mentally disordered people out of the jurisdiction as more humane than placing them under arrest for minor offenses, such as disorderly conduct or public intoxication.…”
Section: Mentally Disordered Persons and Police Coercionmentioning
confidence: 99%
“…Original Research O ver the years, an increase in the number of police interventions involving people with mental illness has been reported. [1][2][3] Despite this increase, people with mental illness represent a small proportion of all police interactions with citizens. [4][5][6] Nevertheless, some studies have suggested that for minor offences, people with mental illness are more likely than people without mental illness to be arrested.…”
Section: Limitationsmentioning
confidence: 99%